Venopulmonary extracorporeal membrane oxygenation for right ventricular support as a bridge to lung transplantation: A narrative review - Phan Quang Thuan; Nguyen Hoai Nam; Nguyen Hoang Dinh (SAGE Open Medicine)
This review evaluates the effectiveness of veno-pulmonary support with an oxygenator using extracorporeal membrane oxygenation as a bridge to lung transplantation strategy in patients undergoing veno-venous extracorporeal membrane oxygenation while awaiting lung transplantation. Examining indications, contraindications, and clinical outcomes, the study highlights potential benefits, drawing insights from successful cases in South Korea and the United States. Despite limited sample sizes, veno-pulmonary support with an oxygenator using extracorporeal membrane oxygenation emerges as a promising approach for further investigation in lung transplantation support. The review emphasizes its role in improving hemodynamic status, preventing complications during extended waiting periods, and presenting a cost-effective alternative to traditional methods, especially in developing countries. While in-hospital mortality rates range from 0% to 10%, comparable to other approaches, cautious optimism surrounds veno-pulmonary support with an oxygenator using extracorporeal membrane oxygenation, urging expanded research to solidify its standing in enhancing patient outcomes, reducing costs, and promoting transplant success.